Evaluation of photoreceptor features in retinitis pigmentosa with cystoid macular edema by using an adaptive optics fundus camera. - Shohei Kitahata; Kiyoko Gocho; Naohiro Motozawa; Satoshi Yokota; Midori Yamamoto; Akiko Maeda; Yasuhiko Hirami; Yasuo Kurimoto; Kazuaki Kadonosono; Masayo Takahashi (PLoS ONE, 2024)
Objective Cystoid macular edema (CME) in retinitis pigmentosa (RP) is an important complication causing visual dysfunction. We investigated the effect of CME on photoreceptors in RP patients with previous or current CME, using an adaptive optics (AO) fundus camera. Methods We retrospectively observed the CME and ellipsoid zone (EZ) length (average of horizontal and vertical sections) by optical coherence tomography. The density and regularity of the arrangement of photoreceptor cells (Voronoi analysis) were examined at four points around 1.5° from superior to inferior and temporal to nasal. We also performed a multivariate analysis using CME duration, central macular thickness and transversal length of CME. Results We evaluated 18 patients with previous or current CME (18 eyes; age, 48.7 ± 15.6 years) and 24 patients without previous or current CME (24 eyes; age, 46.0 ± 14.5 years). There were no significant differences in age, logMAR visual acuity, or EZ length. In groups with and without CME, cell density was 11967 ± 3148 and 16239 ± 2935 cells/mm2, and sequence regularity was 85.5 ± 3.4% and 88.5 ± 2.8%, respectively; both parameters were significantly different. The correlation between photoreceptor density and age was more negative in group with CME. The CME group tended toward greater reductions in duration of CME. Conclusion Complications of CME in RP patients may lead to a decrease in photoreceptor density and regularity. Additionally, a longer duration of CME may result in a greater reduction in photoreceptor density.